THE USE OF MOBILE PHONE FEATURES BY EFL STUDENTS IN A PRIVATE UNIVERSITY IN JAKARTA - Dinda Ismu Asyifa; Silih Warni; Cahya Komara (UICELL, 2019)
The study investigated features of mobile phone that EFL students potentially use as one as explores their perception toward mobile phone features. Located in one private university in Jakarta (English major and non-English major), this research focused to answer two main questions; 1) what are the features of mobile phone that EFL students’ mostly use to support their English learning? and 2) what are EFL students’ perceptions towards the use of mobile phones features in English learning context? To be able to answer the questions, the quantitative survey method was used by involving 200 students as respondents using Google form questionnaire online. After the data was collected, the researcher calculated and analyzed using IBM SPSS 24 to find mean and percentage. The result of questionnaire showed that students truly use mobile phone features for learning English with the most features that they used were MP3 Players for listening to English music. Next features used by students were Internet Browser, Educational Application, Video Recorder-Application, Game, Camera-Social Media Application, SMS, E-mail, Audio Recorder, and the last is Video Recorder. Meanwhile, from perception questionnaire, the students clearly stated that they enjoyed learning English by using mobile phone features. They strengthened mobile phone features can help them in self-learning than traditional learning.